How to build a pandemic resilient agrifood system? A review of policy lessons from COVID-19 in Bangladesh - Amjath-Babu, Tharayil Shereef; Timsina, Jagadish; Krupnik, Timothy J.; Bhandari, Humnath (International Maize and Wheat Improvement Center, 2022)
The COVID-19 pandemic impacted most of the Bangladesh population and almost all sectors of its economy, including the agriculture and food systems. The Government of Bangladesh (GoB) and development partners took measures to prevent the spread of the virus and keep the agriculture and food systems running, and farmers and communities adopted local techniques as resilience measures to adapt to and lessen the effect of the virus. This review attempts to synthesize the knowledge on impacts of COVID-19 on Bangladesh agriculture and food systems, and document government's and development partners' policy responses and measures to COVID-19 to mitigate the impacts and farmers' coping strategies as effective resilience measures. The aim here is to provide a comprehensive picture of impacts and policy lessons to the Bangladesh government and development partners to effectively manage any future pandemics such as COVID-19 in the country and in developing countries of Asia. The core lesson is that agriculture needs a transformation to technology intensive (both digital and non-digital), efficient supply chains (i.e., shorter value chains), mechanization, farmer organizations led, and consumer connected (e.g., online platforms and direct marketing channels) with various kinds of resilience measures, including information sharing systems, financial mechanisms and social safety nets. A diversified approach is required for perishable and non-perishable commodities. There is also need of international effort to minimize trade and supply disruption and prevention of export ban and similar policies to reduce the impact on food system and associated livelihoods.